PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN (LP2B) SEBAGAI UPAYA UNTUK MEWUJUDKAN KEMANDIRIAN PANGAN PADA PELAKSANAAN PERDA NOMOR 9 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH KABUPATEN BOYOLALI TAHUN 2011-2031 - HARTATI, TRI (Dinamika Hukum, 2019)
The results of the study show that sustainable agricultural land protection as an effort to realize food self-sufficiency has problems based on Regional Regulation No. 17 of 2016 concerning the Protection of Sustainable Food Agriculture Land. Boyolali Regency implementation of sustainable agricultural land protection as an effort to realize food self-sufficiency has only arrived at the location identification stage and the existence of a regional regulation that regulates it. The location identification carried out by Bappeda in 2016 resulted in a Spatial Planning for Sustainable Agriculture Land Protection document, but until now it has not been confirmed in the form of regional regulations. So that the next activity process cannot be carried out optimally, such as control and supervision activities that have not been maximized despite having the Boyolali District Regulation Number 17 of 2016 concerning the Protection of Sustainable Food Agriculture Land. The strategy that needs to be taken to achieve sustainable agricultural land protection as an effort to realize food independence in Bupatei Regency is from an ecological aspect. This shows that the protection of sustainable agricultural land is closely related to environmental sustainability. The main priority efforts are soil and water conservation, because the impact of soil damage does not directly affect agricultural production, but without conservation efforts, high agricultural land productivity and agricultural enterprises will not be sustainable. Key words: Protection, Sustainable Food Agriculture Land (LP2B) Realizing Food Independence